A Transtextual Approach to Lexicographic Functions - Gouws, Rufus H. (Lexikos, 2007)
Abstract: The development of theoretical lexicography clearly indicates a movement towards a more general recognition of the role of lexicographic functions. A consistent application of lexicographic functions has a major influence on the contents of dictionary articles but also on the data distribution and even the typological classification. In the discussion of lexicographic functions, the emphasis has primarily been on the central list of dictionaries. This article proposes an approach where outer texts are also selected and compiled in order to make an active contribution to achieving the lexicographic functions of a given dictionary. A distinction is made between function-adhering and non-function-adhering outer texts. The function-adhering outer texts can further be divided into integrated and non-integrated function-adhering outer texts. With reference to the data distribution programme of a dictionary, it is suggested that in the planning of every dictionary, provision should be made for a function allocation programme. This will ensure that the identified functions of a given dictionary will be realised in both the central list and the outer texts.Keywords: BACK MATTER TEXTS, CENTRAL LIST, COGNITIVE FUNCTION, DATA DISTRIBUTION, FRAME STRUCTURE, FRONT MATTER TEXTS, FUNCTION ALLOCATION PROGRAMME, FUNCTION-ADHERING OUTER TEXTS, FUNCTIONAL TEXT PARTS, INTEGRATED FUNCTION-ADHERING OUTER TEXTS, LEXICOGRAPHIC FUNCTIONS, NON-FUNCTION-ADHERING OUTER TEXTS, NON-INTEGRATED FUNCTION-ADHERING OUTER TEXTS, OUTER TEXTS, TEXT PRODUCTION, TEXT RECEPTION, TRANSTEXTUAL APPROACHOpsomming: 'n Transtekstuele benadering tot leksikografiese funksies. Die ontwikkeling van die teoretiese leksikografie toon 'n duidelike beweging in die rigting van 'n groter erkenning aan die rol van leksikografiese funksies. 'n Konsekwente toepassing van leksiko-grafiese funksies het 'n ingrypende invloed op die inhoud van woordeboekartikels maar ook op die dataverspreiding en selfs op die tipologiese klassifikasie. Tot dusver was die klem in die gesprek oor leksikografiese funksies veral op die sentrale teks van woordeboeke. Hierdie artikel bepleit 'n benadering waar die buitetekste ook gekies en saamgestel moet word om aktief by te dra tot die bereiking van 'n bepaalde woordeboek se leksikografiese funksies. 'n Onderskeid word gemaak tussen funksienakomende en niefunksienakomende buitetekste. Die funksienakomende buitetekste kan op hulle beurt weer onderverdeel word in geÃ¯ntegreerde en niegeÃ¯ntegreerde funksienako-mende tekste. Na aanleiding van die dataverspreidingsprogram van woordeboeke word voorgestel dat daar in die beplanning van elke woordeboek ook voorsiening gemaak word vir 'n funksietoe-kennende program. Dit sal verseker dat die geÃ¯dentifiseerde funksies van 'n bepaalde woordeboek in sowel die sentrale teks as die buitetekste verwerklik word.Sleutelwoorde: AGTERTEKSTE, BUITETEKSTE, DATAVERSPREIDING, FUNKSIENA-KOMENDE BUITETEKSTE, FUNKSIETOEKENNENDE PROGRAM, FUNKSIONELE TEKSDELE, GEÃNTEGREERDE FUNKSIENAKOMENDE BUITETEKSTE, KOGNITIEWE FUNKSIE, LEKSI-KOGRAFIESE FUNKSIES, NIEFUNKSIENAKOMENDE BUITETEKSTE, NIEGEÃNTEGREERDE FUNKSIENAKOMENDE BUITETEKSTE, RAAMSTRUKTUUR, SENTRALE TEKS, TEKSPRO-DUKSIE, TEKSRESEPSIE, TRANSTEKSTUELE BENADERING, VOORTEKSTE